Elephas religiosus. Variations grecques, romaines, païennes, juives et chrétiennes sur le thème de la religiosité animale - Gilles Courtieu (Frontière·s)
The status of animals and their relationship to humans was much debated in pagan, Jewish, and Christian antiquity. Against the prevailing consensus, some authors went so far as to acribe religious behaviour to certain animals, selecting the most rational among them. According to a story written by King Juba II and later taken up by Pliny the Elder, elephants, for instance, were suspected to perform rituals, prophecy and oaths. Overall, these anthropomorphic representations proved to be a means of observing how humans might have originally conceived religiosity–before thinking of religion itself.